Exploitation and conservation of Harp and Hood Seals - Sergeant, D. E. (Polar Record, 1965)
Great improvements have taken place in the last few years in the dressing of hair seal pelts for furs and the market for these furs has diversified and expanded. Consequently, the catching of hair seals of all species has intensified and the stocks of Harp Seals ( Pagophilus groenlandicus )and Hood Seals ( Cystophora cristata) of the North Atlantic, particularly, are under heavy pressure